A post-translational modification in the GGQ motif of RF2 from Escherichia coli stimulates termination of translation - Dinçbas-Renqvist, Vildan (Oxford University Press, 2000)
A post-translational modification affecting the translation termination rate was identified in the universally conserved GGQ sequence of release factor 2 (RF2) from Escherichia coli, which is thought to mimic the CCA end of the tRNA molecule. It was shown by mass spectrometry and Edman degradation that glutamine in position 252 is N(5)-methylated. Overexpression of RF2 yields protein lacking the methylation. RF2 from E.coli K12 is unique in having Thr246 near the GGQ motif, where all other sequenced bacterial class 1 RFs have alanine or serine. Sequencing the prfB gene from E.coli B and MRE600 strains showed that residue 246 is coded as alanine, in contrast to K12 RF2. Thr246 decreases RF2-dependent termination efficiency compared with Ala246, especially for short peptidyl-tRNAs. Methylation of Gln252 increases the termination efficiency of RF2, irrespective of the identity of the amino acid in position 246. We propose that the previously observed lethal effect of overproducing E.coli K12 RF2 arises through accumulating the defects due to lack of Gln252 methylation and Thr246 in place of alanine.